Benefits of Low Dosage of Colchicine Administration on Decreasing Rehospitalization and Mortality within 30 Days in Post-Acute Coronary Syndrome Patients with ST-Segment Elevation Undergoing Percutaneous Coronary Intervention - Satrijo, Budi; Ashari, Yordan Wicaksono; Rohman, Mohammad Saifur; Anjarwani, Setyasih; Tjahjono, Cholid Tri (Universitas Brawijaya, 2023)
Background: The role of inflammation in myocardial infarction and post-infarction MI remodeling has become a concern for the development of treatment in the last decade. Colchicine can prevent increased inflammation during acute injury.Objective: This study focused on the role of colchicine as an on-top medical treatment, hoping it can reduce mortality and short-term rehospitalization in patients with STEMI.Methods: 347 AMI patients (18-80 year old adults) who visited RSUD dr. Saiful Anwar Malang, between February 2022 and January 2023, participated in this prospective, randomized, double-blinded, placebo-controlledexperiment. Patients were split into two groups and given either a placebo orÂ colchicine 0.5 mg daily for a month. Standard medical therapy was administered concurrently to both groups as an approachable guideline. The study endpoints were mortality and rehospitalization rates.Result: After one month of follow-up, there was a reduction in rehospitalization due to cardiovascular causes (2 [1.3%] vs. 4 [2.7%], HR 3.42 [1.36-8.56], p<0.05), which was significant in the treatment group compared to the control group. Also, there was a reduction in all-cause mortality, but not statistically significant (2 [1,3% v 3 [2,0%], HR 3,38 [0,53-7,48], p>0,05). In the treated group, there was also a lower non-cardiovascular rehospitalization rate compared to placebo, but not significant (4 [2.6%] vs. 7 [4.7], HR 0.42 [0.15-1.02], p<0.05).Conclusion: The administration of low-dose colchicine for one month has shown benefits in reducing rehospitalization in patients with STEMI who receive PCI therapy.